The Impact of Movement Control Order (MCO) during Pandemic COVID-19 on Local Air Quality in an Urban Area of Klang Valley, Malaysia - Mohd Shahrul Mohd Nadzir; Maggie Chel Gee Ooi; Kemal Maulana Alhasa; Mohd Aftar Abu Bakar; Anis Asma Ahmad Mohtar; Mohd Fadzil Firdzaus Mohd Nor; Mohd Talib Latif; Haris Hafizal Abd Hamid; Sawal Hamid Md Ali; Noratiqah Mohd Ariff; Johary Anuar; Fatimah Ahamad; et al. (Aerosol and Air Quality Research)
Abstract The world is currently going through the COVID-19 pandemic which has caused hundreds of thousands of deaths in just a few months. Considering the need for lockdown measures, most countries, including Malaysia, have implemented ‘Movement Control Orders’ (MCOs) as a prevention step to reduce the deadly spread of this disease. Local and worldwide media have reported the immediate improvement of air quality due to this event. Nevertheless, data on the effects of MCOs on air quality at local scales are still sparse. Here, we investigate changes in air quality during the MCO at an urban area using the air sensor network AiRBOXSense which measures monoxide (CO) and particulate matter (PM2.5 and PM10). In this study, air pollutant data during normal days were compared with MCO days using a reference analyser and AiRBOXSense. The results showed that the levels of the measured pollutants dropped by ~20 to 60% during the MCO days at most locations. However, CO in Kota Damansara (KD) dropped to 48.7%, but PM2.5 and PM10 increased up to 60% and 9.7% respectively during MCO days. Local burning activities in the residential area of KD are believed to be the main cause of the increased PM levels. This study has proven that air pollutant levels have significantly fallen due to the MCO. This air quality level information showed that the reduction of air pollutants can be achieved if traffic and industry emissions are strictly controlled.